1989
DOI: 10.1007/bf02935917
|View full text |Cite
|
Sign up to set email alerts
|

Origins of resistances to rust and late leaf spot in peanut (Arachis hypogaea, Fabaceae)

Abstract: 7'hcc~ulti~utedpc~a,r1~/ (Arachis hypogaea. Fubaccac) is belic~ved to have orlginutcjd ulorrg I/?(, C~U S I C~I I slo/)c,s (?f ihr ..lnrl(s in Bo111.ia und northerr1 Argentina. The crop 1s t~orc groLt,tr thronghout i r o~~i c~u l utid warm tonpiJralr regron.c. .4rnong diseases uttac.krn,q pc,ut~lrrs, rlitr cwlr.,c~/ hjl Puccinia arachidis arid larr, Ieuf'spot cuuscd hj, Phaeoisariopsis personata urea flic r?io.sl rt?iportan/ and dcstrurttvc~ on a ~, o r l d~, i d r .\c,olc. noti? pa//iogc,tr~, rr,stric./cd rn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 18 publications
0
40
0
1
Order By: Relevance
“…Among the biotic stresses, two foliar diseases viz. Late leaf spot (LLS, causal organism Phaeoisariopsis personata) and rust (causal organism Puccinia arachidis) cause more than 50% yield losses (Subrahmanyam et al, 1989), These two diseases occur simultaneously and drastically reduce the yield and quality of haulm. Thus, it necessitated for the identification and utilization of resistant sources in the breeding programmes.…”
Section: Issn: 2319-7706 Volume 7 Number 08 (2018)mentioning
confidence: 99%
“…Among the biotic stresses, two foliar diseases viz. Late leaf spot (LLS, causal organism Phaeoisariopsis personata) and rust (causal organism Puccinia arachidis) cause more than 50% yield losses (Subrahmanyam et al, 1989), These two diseases occur simultaneously and drastically reduce the yield and quality of haulm. Thus, it necessitated for the identification and utilization of resistant sources in the breeding programmes.…”
Section: Issn: 2319-7706 Volume 7 Number 08 (2018)mentioning
confidence: 99%
“…Subrahmanyam et al (1989) evaluated 96 accessions of wild Arachis species for reactions to late leaf spot and observed that lesions were formed on all accessions, but lesions were small and nonsporulating on all accessions of sections Erectoides, Triseminatae, Extranervosae, Rhizomatosae, and Caulorrhizae. Lesions with diameters ranging from 0.16 to 1.0 mm were, however, found in section Arachis.…”
Section: Breedingmentioning
confidence: 99%
“…Resistance is present in A. hypogaea, with most of the resistant accessions being of subspecies fastigiata (Subrahmanyam et al 1989). Inheritance studies indicated the presence of two or three recessive genes in some crosses, with evidence for epistatic interactions, and with resistance being accompanied by slowing down of disease development (Subrahmanyam et al 1983b).…”
Section: Breedingmentioning
confidence: 99%
“…Groundnut is a rich source of protein, dietary fiber, minerals, and vitamins 13 . Groundnut production all over the world is hampered by several biotic stresses that result in severe yield reduction 18,21 . Of different soilborne diseases affecting its production, collar rot (Aspergillus niger) 1 ; stem rot (Sclerotium rolfsii) 11 ; and bacterial wilt (Ralstonia solanacearum) 9 are the devastating ones in all crop growing areas of the world.…”
Section: Introductionmentioning
confidence: 99%